'It's Not a Lot of Boring Old Gits Sitting about Remembering the Good Old Days': The Heritage and Legacy of the 1987 Caterpillar Factory Occupation in Uddingston, Scotland. Issue 1 (1st April 2021) - Gibbs, Ewan
Abstract : This paper examines the construction of a factory occupation's 'usable past'. It analyses how the political culture of the multinational 'branch plant' has combined with the optics of class and nation that predominate in accounts of Scottish deindustrialization. During 2017, the Caterpillar Workers Legacy Group commemorated the occupation of Caterpillar's tractor plant in Uddingston, Lanarkshire, thirty years earlier. The occupation endured for 103 days, becoming a labour-movement cause célèbre. Commemoration included workforce reunions, museum exhibitions, drama performances and an anniversary debate in the Scottish Parliament. Legacy Group members archived the occupation 'from below', including by recording oral testimonies. The occupation was rooted in a tradition of 'rank-and-filist' factory trade unionism and sustained by a left-wing activist infrastructure which shaped the dispute's contemporary framing and historical legacy. A culture of radical labourism that rejected managerial authority and profit-making as the factory's basis for operation enthused the occupation's defence of the right to work. These actions now form the basis for embedding a political and cultural 'working-class presence' long after Caterpillar departed from Uddingston. The (co-) production of labour-movement heritages is a complex process, shaped by enduring activist repertoires as well as dominant public memories.